Robotic radiosurgery of head and neck paragangliomas: a single institution experience. Issue 2 (24th May 2017) - Tosun, İlker and Atalar, Banu and Şahin, Bilgehan and Güngör, Görkem and Aydin, Gökhan and Yapici, Bülent and Özyar, Enis
Abstract: Aim: CyberKnife ® is a robotic stereotactic radiotherapy system. The aim of this study is to evaluate the effectiveness and the safety of CyberKnife ® on treating head and neck paragangliomas and to report our results. Methods: Between March 2009 and June 2014, 12 patients with head and neck paragangliomas have been referred to our clinic: in three cases had jugular paragangliomas, five cases had carotid body paragangliomas and three cases had tympanic paragangliomas. One patient had bilateral neck paragangliomas (right neck; carotid body paraganglioma, left neck; jugular pargangliomas). All of them received fractionated stereotactic radiotherapy with CyberKnife ® up to a total median dose of 24 Gy (reference isodose 67–90%). The median tumor volume was 35.5 cc (range, 5.3—113.8 cc). The median follow up was 30 months (range, 0–66 months). Local tumor control was assessed according to RECIST criteria on follow‐up imaging studies. Results: There were no acute or late toxicity related with stereotactic radiotherapy after treatment. No local tumor progression was observed on magnetic resonance imaging and none of our patients showed progressive clinical status. Seven tumors shrinked in size (54%). Five tumors (46%) had stable size during follow up. Local control rate was 100%. Conclusion: Stereotactic radiotherapy is a good alternative to surgery for the treatment of head and neck paragangliomas coming up with a clear benefit of acute and late side effects. CyberKnife ® seems to be a safe and efficient system treating head and neck paragangliomas.